Development of a system for monitoring vibration accelerations based on the raspberry pi microcomputer and the ADXL345 accelerometer - Holovatyy, Andriy; Teslyuk, Vasyl; Iwaniec, Marek; Mashevska, Marta (Eastern-European Journal of Enterprise Technologies, 2017)
A system for monitoring and analysis of the vibration acceleration spectrum based on the Raspberry Pi 3 microcomputer and the triaxial digital ADXL345 accelerometer for a real-time operation has been developed. In the process of implementation of the system, the structure and algorithm of functioning of the system for monitoring and analysis of the vibration acceleration spectrum were constructed. The designed structure is based on the modular principle which enables fast improvement of the system. A specialized system software has been developed. It includes a driver for adjusting, collecting and processing the accelerometer data and the corresponding software for plotting vibration acceleration signals in time and frequency domains. Moreover, the software is based on the use of free programs, it features the ability of real-time study of the vibration effect on an object, determining vibration amplitudes and frequencies, plotting graphs of vibration change in time, calculating discrete Fourier transforms and obtaining spectra. The physical model of the system for monitoring and analysis of the vibration acceleration spectrum has been developed. It includes the Raspberry Pi 3, Model B single-board microcomputer, the ADXL345 triaxial digital accelerometer, the liquid-crystal display and is characterized by a low cost and a wide functionality. The system makes it possible to analyze vibration parameters in order to predict and prevent possible accidents, thus reducing the costs associated with the failure of the cutting tools, expensive parts and assemblies of the CNC machine